(untitled) (Journal of EAHIL, 2019)
This paper aims to help medical librarians spot potential friction with a would-be employer. This is achieved by naming the most important aspects to focus on while choosing a new position, in order to avoid disappointment in a new role. It summarises anecdotal evidence based on personal experience.